Attention Deficit Hyperactivity Disorder (ADHD) - Londhe, Ashwini Gajanan (THE PRIMARY TEACHER, 2025)
ADHD is a neuro-behavioural disorder which includes attention difficulty, hyperactivity and impulsiveness. It is a chronic brain condition that causes executive dysfunction, hence, it disrupts a person's motor skills, and intellectual, speech, emotional, social and sexual development. It impacts a child's life starting from home, in schools and even in social situations. This paper highlights various symptoms, stages of early detection along with the causes of ADHD. The overall organisational and management skills also become challenged. The teachers can detect and also help parents cater to this disorder by understanding the ways to communicate and act upon these symptoms through the right kind of socialisation and professional help which can make the child's life much easier.